Ultrafast water sensing and thermal imaging by a metal-organic framework with switchable luminescence - Chen, Ling; Ye, Jia-Wen; Wang, Hai-Ping; Pan, Mei; Yin, Shao-Yun; Wei, Zhang-Wen; Zhang, Lu-Yin; Wu, Kai; Fan, Ya-Nan; Su, Cheng-Yong (Nature communications, 2017)
A convenient, fast and selective water analysis method is highly desirable in industrial and detection processes. Here a robust microporous Zn-MOF (metal–organic framework, Zn(hpi2cf)(DMF)(H 2 O)) is assembled from a dual-emissive H 2 hpi2cf (5-(2-(5-fluoro-2-hydroxyphenyl)-4,5-bis(4-fluorophenyl)-1 H -imidazol-1-yl)isophthalic acid) ligand that exhibits characteristic excited state intramolecular proton transfer (ESIPT). This Zn-MOF contains amphipathic micropores (<3 Å) and undergoes extremely facile single-crystal-to-single-crystal transformation driven by reversible removal/uptake of coordinating water molecules simply stimulated by dry gas blowing or gentle heating at 70 °C, manifesting an excellent example of dynamic reversible coordination behaviour. The interconversion between the hydrated and dehydrated phases can turn the ligand ESIPT process on or off, resulting in sensitive two-colour photoluminescence switching over cycles. Therefore, this Zn-MOF represents an excellent PL water-sensing material, showing a fast (on the order of seconds) and highly selective response to water on a molecular level. Furthermore, paper or in situ grown ZnO-based sensing films have been fabricated and applied in humidity sensing (RH<1%), detection of traces of water (<0.05% v/v) in various organic solvents, thermal imaging and as a thermometer. Fast and sensitive detection of water molecules in organic solvents and gases remains an important challenge. Here, Pan and co-workers design a metal-organic framework capable of ultrafast and reversible water sensing by photoluminescence switching via an excited state intramolecular proton transfer mechanism.